1993
DOI: 10.1177/088626093008001008
|View full text |Cite
|
Sign up to set email alerts
|

Victim Reactions During Rape/Sexual Assault

Abstract: Overt signs of victim resistance during rape are critical issues in the handling of and recovery from rape/sexual assault. However, a substantial number of victims do not resist the attacker in any way. Tonic immobility (TI), a well-known involuntary, reflexive response to fear-inducing stimuli, may aid in explaining the paralysis and “freezing” of many rape victims. In the present study, rape survivors were classified as immobile, intermediate, or mobile, based on a self-report measure. The immobile group man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(47 citation statements)
references
References 10 publications
0
43
0
Order By: Relevance
“…Theoretically, some models distinguish freezing from tonic immobility, with tonic immobility, or "death feigning" taking place after contact with the predator, when fight, flight, or freezing are no longer options that increase survival chances (Eilam, 2005;Marx, Forsyth, Gallup, Fusé, & Lexingon, 2008). Human retrospective studies have found peritraumatic tonic immobility to be associated with later impairment like posttraumatic stress disorder (Bovin et al, 2008;Galliano, Noble, Puechl, & Travis, 1993;Heidt, Marx, & Forsyth, 2005). The distinction between freezing and tonic immobility is an interesting one that merits further investigation with longitudinal designs.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, some models distinguish freezing from tonic immobility, with tonic immobility, or "death feigning" taking place after contact with the predator, when fight, flight, or freezing are no longer options that increase survival chances (Eilam, 2005;Marx, Forsyth, Gallup, Fusé, & Lexingon, 2008). Human retrospective studies have found peritraumatic tonic immobility to be associated with later impairment like posttraumatic stress disorder (Bovin et al, 2008;Galliano, Noble, Puechl, & Travis, 1993;Heidt, Marx, & Forsyth, 2005). The distinction between freezing and tonic immobility is an interesting one that merits further investigation with longitudinal designs.…”
Section: Discussionmentioning
confidence: 99%
“…Burgess and Holmstrom (1976) classified such behaviors during sexual assault as falling into one or more categories: cognitive assessment strategies (e.g., mentally assessing the situation, attempting to remain calm and devising a plan of escape), verbal strategies (e.g., yelling, screaming, bargaining) and physical actions (e.g., fighting back). It has become increasingly evident, however, that some women respond to the attack by exhibiting a physiological response characterized by involuntary immobility or freezing (Burgess & Holmstrom, 1976;Galliano, Noble, Travis, & Puechl, 1993). This response, in turn, is loosely characterized by the feeling of being paralyzed or ''frozen'' during the attack, accompanied by an inability to physically resist or call for help.…”
Section: Immobility Reactions During Sexual Assaultmentioning
confidence: 97%
“…It is not surprising, therefore, that several researchers and professionals who work with sexual assault survivors recognize the immobility reaction, more commonly referred to as ''rape-induced paralysis,'' as a distinct response that frequently occurs during sexual assault (Carter, Prentky, & Burgess, 1988, Suarez & Gallup, 1979, Ullman & Knight, 1995. Galliano et al (1993) conducted preliminary research on immobility reactions displayed by women who survived completed rapes. They classified the behavior of study participants during the assault as immobile, mobile or intermediate, based on participants' retrospective self-reports.…”
Section: Tonic Immobility In Sexual Assault Survivorsmentioning
confidence: 97%
See 2 more Smart Citations